Sexual Selection and the Treatment of Predecessors’ Progeny by Replacement Mates - Daly, Martin; Perry, Gretchen (Frontiers in Psychology, 2022)
Darwin’s theory of sexual selection provides a useful framework for understanding the behavior of stepparents. A nonhuman animal whose new mate has dependent young may kill, ignore or adopt the predecessor’s progeny. The third option has been interpreted as courtship ("mating effort"), and whether selection favors such investment over killing or ignoring the young apparently depends on aspects of the species-typical ecology and demography. The tripartite categorization of responses is a simplification, however: There is variability both within and between species along a continuum from rejection to "full adoption". The average stepparent invests less than the average birth parent, but more than nothing. Human stepparents have often been found to kill young children at higher rates than birth parents, but stepparental infanticide cannot plausibly be interpreted as a human adaptation, both because it is extremely rare and because it is almost certainly more likely to reduce the killer's fitness than to raise it. How sexual selection theory remains relevant to human stepparenting is by suggesting testable hypotheses about predictors of the variability in stepparental investment.